Do not resuscitate: a comparative study between the position in England and Malaysia in relation to unconscious terminally ill patient / Shahida Najme Khir, Adeline Ayub Tabad and Nurul Hafizan Abdul Wahid. - Najme Khir, Shahida; Ayub Tabad, Adeline; Abdul Wahid, Nurul Hafizan (Faculty of Law, 2008)
The rising tide of litigation means that no doctor is immune from medico-legal liability for their actions. Clinical negligence claims may threaten the reputation and career of even the most eminent practitioner. Therefore this research aims to emphasize the need to have DNR Order and guidelines or policies for unconscious terminally ill patient in Malaysia. Briefly, the topic of Do Not Resuscitate has received a lot of criticism in the overseas and it is a sensitive issue to be discussed especially among doctors, patients and patients family. Therefore this research paper will first explore the application and controversy of cardiac arrest procedure (CPR) and the law of consent to medical treatment. The next chapter provides a research on the liability of doctor and an existing guideline in relation to unconscious terminally ill patient and DNR Order. Chapter four suggests the future recommendation of a having a DNR Order in Malaysia and introduce ways and regulations for unconscious terminally ill patient. This project is finally concluded by pointing out that there should be a set of guidelines or policy Do Not Resuscitate in. Since clinical decisions involve the assessment of facts and values, it is important that doctors, and indeed all health professionals, are able to give reasons for the decisions they make and the actions they take. The law demands such reasons.